Application of probiotics and prebiotics for promoting growth of Tiger shrimp (Penaeus monodon): an approach to eco-friendly shrimp aquaculture - Bir, J; Golder, MR; Biswas, SK; Islam, SS; Kumar, R; Huq, KA (International Journal of Agricultural Research, Innovation and Technology, 2021)
The current study has been conducted to evaluate the growth performance of shrimp (Penaeus monodon) by applying eco-friendly culture mechanism like prebiotics and probiotics. The experiment was carried out for 95 days in different shrimp farms at coastal district of Bagerhat, Bangladesh. Three different treatments viz., probiotic treated as T1, prebiotics treated as T2 and both probiotics and prebiotics as T3 with a control group were designed to conduct the experiment. The size of the experimental ponds was five acre and the stocking density was 4/m2 in each treatment. CP NASA shrimp feed (32% protein) was given thrice in a day during the study period. After 95 days of culture period, the maximum weight gain was observed at T3 (33.78±0.18 g) whereas the minimum weight gain was observed at control group (25.69±0.10 g). The survival rate was the highest in T3 (89.01%) followed by T2 (75.51%) and T1 (53.44%) and the lowest rate was observed in control group (50.88%). Overall production was higher in T3 (833.78 kg ha-1) compared to T2 (553.40 kg ha-1), T1 (447.84 kg ha-1) and Control group (310.57 kg ha-1). pH value was found to maximum in T3 (7.71±0.08) and it was minimum in T1 (7.41±0.10). In addition, the maximum TAN value was found to be 2.22±0.19 mg L-1 in C pond and it was minimum in T3 (0.32±0.06 mg L-1). Therefore, it could be concluded that combine application of probiotics and prebiotics might be the reliable media to enhance production of shrimp by maintaining eco-friendly environment in aquaculture. Int. J. Agril. Res. Innov. Tech. 10(2): 15-20, December 2020